2006
DOI: 10.1139/g06-079
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic diversity in cultivars of white clover (Trifolium repensL.) detected by SSR polymorphisms

Abstract: White clover (Trifolium repens L.) is an important temperate pasture legume that plays a key role as a companion to grass species, such as perennial ryegrass (Lolium perenne L.). Due to the outbreeding nature of white clover, cultivars are highly heterogeneous. Genetic diversity was assessed using 16 elite cultivars from Europe, North and South America, Australia, and New Zealand. Fifteen simple sequence repeat markers that detect single, codominant polymorphic genetic loci were selected for the study. The gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 63 publications
(56 reference statements)
8
37
0
Order By: Relevance
“…As individual alleles are unable to be conWdently attributed to a speciWc sub-genome within the polyploid samples, alleles from all samples were scored in a dominant manner and converted into a binary (presence/absence) matrix. The polymorphism information content of each SSR marker was calculated as a measure of heterozygosity (Nei 1973) within each locus and was calculated as described by George et al (2006).…”
Section: Ssr Genotypingmentioning
confidence: 99%
“…As individual alleles are unable to be conWdently attributed to a speciWc sub-genome within the polyploid samples, alleles from all samples were scored in a dominant manner and converted into a binary (presence/absence) matrix. The polymorphism information content of each SSR marker was calculated as a measure of heterozygosity (Nei 1973) within each locus and was calculated as described by George et al (2006).…”
Section: Ssr Genotypingmentioning
confidence: 99%
“…Information on genetic variation in Aquilegia germplasm could also be used to assist genetic mapping, quantitative trait locus (QTL) studies and the design of linkage disequilibrium mapping strategies for marker-trait association (George et al, 2006). Diversity at marker loci is currently the most feasible strategy for characterizing diversity in wild and cultivated germplasm.…”
Section: Introductionmentioning
confidence: 99%
“…White clover is an obligate outbreeding allotetraploid forage legume (2n = 4x = 32) exhibiting high levels of intrapopulation genetic diversity (George et al 2006b) and intragenotype heterozygosity (K枚lliker et al 2001;Jones et al 2003). Although inbred lines based on self-fertile mutants have been developed by single seed descent (Michaelson-Yeates et al 1997) high levels of residual heterozygosity were observed (Jones et al 2003).…”
Section: Introductionmentioning
confidence: 99%